ANALYSIS OF BUSINESS FEASIBILITY OF BIOFLOC METHOD FISH CULTIVATION UNIT AT MUAMALAT NAHDLATUL ULAMA SYARIAH COOPERATIVE KASOMALANG SUBANG - Mutqi Sopiawadi; Tigin Lugiani (STIESA Press, 2022)
Before starting a business, an analysis is needed to determine the feasibility of the business. business feasibility serves to find out whether the business to be run can provide benefits in the future. One of the most important business feasibility analysis is financial analysis. The biofloc business plan to be carried out by the sharia cooperative Muamalat Nadhlatul Ulama needs further financial analysis so that it does not cause losses later. Therefore the purpose of this study is to determine the financial feasibility analysis of the biofloc business plan In this study using the uni analysis of Sharia Cooperatives Muamalat Nadhlatul Ulama, Kasomalang, Subang. Sources of data in this study are primary data and secondary data obtained from interviews, cooperative financial reports, and literature. As well as in this study analyzing financial feasibility using financial ratios such as net profit, profit rate, benefit cost ratio, and payback period. The findings of this study indicate that the biofloc business plan to be carried out by the cooperative is feasible because it can provide a fairly decent profit and return on investment.